Screening the Red Army Faction : historical and cultural memory - Gerhardt, Christina (Bloomsbury Academic, Bloomsbury Publishing Plc, 2018)
"Screening the Red Army Faction: Historical and Cultural Memory explores representations of the Red Army Faction (RAF) in print media, film and art, locating an analysis of these texts in the historical and political context of unfolding events. In this way, the book contributes both a new history and a new cultural history of post-fascist era West Germany that grapples with the fledging republic's most pivotal debates about the nature of democracy and authority; about violence, its motivations and regulation; and about its cultural afterlife. Looking back at the history of representations of the RAF in various media, this book considers how our understanding of the Cold War era, of the long sixties and of the RAF is created and re-created through cultural texts."--Bloomsbury Publishing